SEED PERFORMANCE OF COMMON BEAN AND COWPEA BY PRIMING AND PLANTING DATE - Hasanzadeh, Mohammad; Demir, Ibrahim; Hazrati, Nahid; Taşkin, Mehmet burak; şahin, Özge (Journal of Agricultural Sciences (Belgrade), 2019)
A 2-year farm trial by employing nutrition priming technique on common bean (Sarıkız) and cowpea (Şimal) seeds was performed to assess seed quality and quantity. Priming: (p1) control, (p2) KH2PO4, (p3) ZnSO4 and (p4) KH2PO4+ZnSO4, planting date: (d1) 20 May, (d2) 15 June 2015, (d1) 7 May, (d2) 7 June 2016 were studied on yield (kg ha-1) and crude protein (%) of the mentioned crops in Turkey. In 2015, applications of p3 and p4 (868.8, 834.8), d2 (962.3) and p4d2, p2d2 and p3d2 (1061, 1052, 1028) were significant on seed yield of Sarıkız and p2 and p1 (899.5, 835.9) and d2 (955.9) on yield of Şimal. p4 and p3 (18.7, 18.5), d2 (19.2), and p4d2 (21.3) were significant on protein of Sarıkız and d2 (19.4) on protein of Şimal. In 2016, p3 (2506), d2 (2516) and p3d2 (3650) were significant on yield, and p4 (26.1), d2 (26.8) and p4d2 (28.3) on protein of Sarıkız. p3 (1979.1), d2 (2664.3) and p3d2 (3310.6) were significant on yield, and d1 (24.1) and p3d1 (25.7) on protein of Şimal. Application of Zn and P by seed priming seems to be more effective than traditional fertilization by these elements.